Professional development of academic teachers in the audit culture = Rozwój zawodowy nauczycieli akademickich w kulturze audytu - Szplit, Agnieszka (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Current problems in education include excessive bureaucracy and the need to develop tools to measure the effectiveness of teaching and scientific development. This is evidenced by the measurement procedures commonly implemented for quality of education and constant checking the implementation of intended activities. The pedagogical literature uses terms such as "audit society" or "audit culture" to describe these trends.
Keywords: audit culture; teachers` performance assessment; teacher educators; teacher educators` professional development; kultura audytu; ocena pracy nauczyciela; nauczyciele nauczycieli; rozwój zawodowy nauczycieli